Provincial Needs Assessment to Determine the Current State of Glomerulonephritis Care in Ontario. Issue 1 (September 2019) - Pang, Jocelyn; D'Antonio, Christina; Heale, Esti; Boll, Philip; Blake, Peter; Evans, Jenna M.; Hladunewich, Michelle
Background: Despite its relative rarity, glomerulonephritis (GN) accounts for 20% of prevalent end-stage renal disease patients in Ontario. Early identification and appropriate management of GN to delay progression of disease can reduce patient morbidity and health system costs. As such, a provincial GN needs assessment was conducted to inform on the development of the provincial GN strategic framework in Ontario. Objective: To understand the current state of GN care in Ontario from nephrologist, hospital administrator, and patient and family perspectives. Design: Cross-sectional. Settings: 26 regional renal programs in Ontario. Patients: 23 patients and family members living with GN who do not require renal replacement therapy. Measurements: Patient and family member interviews as well as a survey of nephrologists. Methods: The study included 3 components: (1) interviews with patients and family members, (2) a survey of nephrologists, and (3) interviews with regional renal programs. The Ontario Renal Network provincial office developed the needs assessment questions and the physician survey questions after consultation with practicing nephrologists and hospital administrators. Thematic analysis was used to assess interview data and descriptive statistics to assess survey data. Results: Interviews with patients and family members (n = 23) identified gaps in care related to diagnosis and referral to nephrology care, education and decision-making, and psychosocial supports. The survey of nephrologists (n = 74) identified various issues that contribute to unstandardized GN care across Ontario, including a lack of provincial expertise in providing complex GN care, access to medication, multidisciplinary team support as well as patient education, and psychosocial supports. Interviews with regional renal programs aligned with interview and survey findings (n = 11). Limitations: Interviews with patients and family members were facilitated by 1 interviewer and limited to 20 interviews due to resource limitations. All nephrologists, patients, and family members who participated in the survey and interviews were volunteers and English-speaking, which may have resulted in self-selection bias. Conclusions: The provincial GN needs assessment emphasized the necessity to develop and implement a provincial GN strategy. The strategic framework includes 4 objectives: (1) ensure patients are supported to make informed decisions, (2) establish a provincial model of care, (3) leverage data to enable planning, decision-making, and monitoring of outcomes, and (4) ensure appropriate access to medication. This is the first Ontario strategy to address provincial gaps in GN care.